Association between post-traumatic stress disorder and hypertension in Congolese exposed to violence: a case–control study. Issue 4 (13th April 2022) - Bapolisi, Achille; Maurage, Pierre; Pappaccogli, Marco; Georges, Coralie M.G.; Petit, Géraldine; Balola, Mitterrand; Cikomola, Cirhuza; Bisimwa, Ghislain; Burnier, Michel; Persu, Alexandre; de Timary, Philippe
Abstract : Background: Numerous risk factors have been involved in the pathogenesis of hypertension. The contribution of psychological factors, including post-traumatic stress disorder, remains largely underexplored, despite their potential role in hypertension. Objectives: We compared the prevalence of trauma, post-traumatic stress and other psychological disorders between hypertensive and normotensive patients from Bukavu (Democratic Republic of Congo), a 25-year war-exposed city. Methods and measures: In this case–control study, we assessed past traumatic events with the Stressful-Events-Scale, post-traumatic stress disorder through the post-traumatic diagnostic scale, depression and alcohol use disorder through the MINI-International-Neuropsychiatric-Interview, and emotion regulation through the Emotion-Regulation-Questionnaire in 106 hypertensive and 106 normotensive patients, enrolled at the Bukavu General Hospital. Results: Compared with normotensive controls (73% women, age: 43 ± 14 years, BP: 121 ± 10/75 ± 8 mmHg), hypertensive patients (57% women, age: 42 ± 13 years, BP: 141 ± 12/82 ± 7 mmHg, on a median of two antihypertensive drugs) were exposed to more man-made traumas (61 vs. 13%, P  < 0.001), used more expressive suppression ( P  = 0.05) and less cognitive reappraisal ( P  = 0.02) as emotional regulation strategies. They developed more frequent post-traumatic stress disorder (36 vs. 7%, P  < 0.001) and major depressive disorder (37 vs. 13%, P  = 0.001), often in association with alcohol use disorder (23 vs. 4%, P  < 0.001). In multivariate logistic regression, post-traumatic stress disorder [OR = 3.52 (1.23–6.54)], man-made trauma [OR = 2.24 (1.15–4.12)], family history of hypertension [OR = 2.24 (1.06–4.44)], fasting blood glucose [OR = 1.85 (1.07–3.08)], BMI [OR = 1.28 (1.12–2.92)], expressive suppression [OR = 1.23 (1.11–2.23)] and cognitive reappraisal [OR = 0.76 (0.63–0.98)] were independent predictors of hypertension. Conclusion: In Congolese populations exposed to war, man-made trauma exposure and post-traumatic stress disorder appear to be more tightly related to hypertension than classical hypertension risk factors.